Scattered genomic amplification in dedifferentiated liposarcoma - Nils Mandahl; Linda Magnusson; Jenny Nilsson; Björn Viklund; Elsa Arbajian; Fredrik Vult von Steyern; Anders Isaksson; Fredrik Mertens (Molecular Cytogenetics, 2017)
Abstract Background Atypical lipomatous tumor (ALT), well differentiated liposarcoma (WDLS) and dedifferentiated liposarcoma (DDLS) are cytogenetically characterized by near-diploid karyotypes with no or few other aberrations than supernumerary ring or giant marker chromosomes, although DDLS tend to have somewhat more complex rearrangements. In contrast, pleomorphic liposarcomas (PLS) have highly aberrant and heterogeneous karyotypes. The ring and giant marker chromosomes contain discontinuous amplicons, in particular including multiple copies of the target genes CDK4, HMGA2 and MDM2 from 12q, but often also sequences from other chromosomes. Results The present study presents a DDLS with an atypical hypertriploid karyotype without any ring or giant marker chromosomes. SNP array analyses revealed amplification of almost the entire 5p and discontinuous amplicons of 12q including the classical target genes, in particular CDK4. In addition, amplicons from 1q, 3q, 7p, 9p, 11q and 20q, covering from 2 to 14 Mb, were present. FISH analyses showed that sequences from 5p and 12q were scattered, separately or together, over more than 10 chromosomes of varying size. At RNA sequencing, significantly elevated expression, compared to myxoid liposarcomas, was seen for TRIO and AMACR in 5p and of CDK4, HMGA2 and MDM2 in 12q. Conclusions The observed pattern of scattered amplification does not show the characteristics of chromothripsis, but is novel and differs from the well known cytogenetic manifestations of amplification, i.e., double minutes, homogeneously staining regions and ring chromosomes. Possible explanations for this unusual distribution of amplified sequences might be the mechanism of alternative lengthening of telomeres that is frequently active in DDLS and events associated with telomere crisis.